Population-nosological research biobank of the National Medical Research Center for Therapy and Preventive Medicine: analysis of biosamples, principles of collecting and storing information - O. V. Kopylova; A. I. Ershova; M. S. Pokrovskaya; A. N. Meshkov; I. A. Efimova; Z. Z. Serebryanskaya; A. V. Blokhina; A. L. Borisova; V. A. Kondratskaya; A. S. Limonova; S. А. Smetnev; O. P. Skirko; et al. (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To analyze the structure of clinical data, as well as the principles of collecting and storing related data of the biobank of the National Medical Research Center for Therapy and Preventive Medicine (hereinafter Biobank).Material and methods. The analysis was carried out using the documentation available in the Biobank, as well as the databases used in its work. The paper presents clinical data on biosamples available in the Biobank as of August 18, 2021.Results. At the time of analysis, the Biobank had 373547 samples collected from 54192 patients within 37 research projects. The article presents the analysis of data representation and quantitative assessment of the presence/absence of common diagnoses in clinical projects. Approaches to documenting clinical information associated with biological samples stored in the Biobank were assessed. The methods and tools used for standardization and automation of processes used in the Biobank were substantiated.Conclusion. The Biobank of the National Medical Research Center for Therapy and Preventive Medicine is the largest research biobank in Russia, which meets all modern international requirements and is one of the key structures that improve the research quality and intensify their conduct both within the one center and in cooperation with other biobanks and scientific institutions. The collection and systematic storage of clinical abstracts of biological samples is an integral and most important part of the Biobank’s work.